On the spider genus Cryptachaea from Peru, Bolivia and cave environments in Brazil: a new species, additional descriptions and new records (Araneae, Theridiidae) - Santanna, Manoela; Rodrigues, Everton Nei Lopes; Cizauskas, Igor; Brescovit, Antonio Domingos (Zootaxa, 2019)
In this paper a new species of Cryptachaea Archer, 1946 based on males and females is described from Brazilian caves: Cryptachaea pilar Santanna & Rodrigues, new species from the states of Minas Gerais and São Paulo. The females of Cryptachaea parana (Levi, 1963) and C. schneirlai (Levi, 1959) are described and illustrated for the first time. Cryptachaea uviana (Levi, 1963) is synonymized with C. migrans (Keyserling, 1884). The species Cryptachaea alacris (Keyserling, 1884), C. benivia Rodrigues & Poeta, 2015, C. parana (Levi, 1963) and C. schneirlai (Levi, 1959) are recorded for the first from Brazil; and C. migrans for the first time from Bolivia. Additionally, new records from Brazilian caves are provided for Cryptachaea parana, from the states of Tocantins, Goiás, Minas Gerais, Mato Grosso do Sul and São Paulo; C. schneirlai and C. alacris from the state of Pará; C. dea (Buckup & Marques, 2006) and C. rioensis (Levi, 1963) from Pará and Minas Gerais, C. jequirituba (Levi, 1963) from Minas Gerais and C. benivia from São Paulo.